Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1080/00207590444000401
|View full text |Cite
|
Sign up to set email alerts
|

Teaching of psychology in Brazil

Abstract: P sychology programs were first recognized in Brazilian universities during the mid-20th century. Prior to that, psychology had been taught in conjunction with other programs such as medicine, law, and education. The growth of psychology programs has been rapid in the last 25 years. From the time the Brazilian government first established a 5-year degree program in 1962, the number of psychology programs regulated by the Ministry of Education has increased to about 150. Graduate programs, established in 1965 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…The current findings suggest that there is an urgent need for qualified academic personal, especially in private universities. Similar differences between state and private universities regarding the quality of psychology education and admission criteria in favor of state universities have also been reported for other developing countries such as Brazil (see Hutz et al, 2006), implying that implementation of quality assurance standards are imperative, especially for the departments in the private universities. Because contemporary psychology education in Turkey has been shaped by academicians who were trained in the United States and Northern Europe, results demonstrated that the basic structure of psychology curriculum in the majority of psychology departments is similar to the U.S. system (see Brewer, 2006;Perlman & McCann, 1999a, 1999bStoloff et al, 2010) in which students begin with basic skills in introductory courses in general psychology, research methods, and statistics and then are exposed to introductory courses in the main subareas in the first 2 years.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The current findings suggest that there is an urgent need for qualified academic personal, especially in private universities. Similar differences between state and private universities regarding the quality of psychology education and admission criteria in favor of state universities have also been reported for other developing countries such as Brazil (see Hutz et al, 2006), implying that implementation of quality assurance standards are imperative, especially for the departments in the private universities. Because contemporary psychology education in Turkey has been shaped by academicians who were trained in the United States and Northern Europe, results demonstrated that the basic structure of psychology curriculum in the majority of psychology departments is similar to the U.S. system (see Brewer, 2006;Perlman & McCann, 1999a, 1999bStoloff et al, 2010) in which students begin with basic skills in introductory courses in general psychology, research methods, and statistics and then are exposed to introductory courses in the main subareas in the first 2 years.…”
Section: Discussionsupporting
confidence: 63%
“…The current findings suggest that there is an urgent need for qualified academic personal, especially in private universities. Similar differences between state and private universities regarding the quality of psychology education and admission criteria in favor of state universities have also been reported for other developing countries such as Brazil (see Hutz et al, 2006), implying that implementation of quality assurance standards are imperative, especially for the departments in the private universities.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The few studies that have systematically assessed the impact of internships on student learning point to the transformation of student attitudes (Sweitzer & King, 2009). Several researchers describe internship components (Bailey, Barber, & Nelson, 2017;Miller, Carr, Utter, Styron, & Steiner, 2017;Motiff & Roehling, 1994;VandeCreek & Fleischer, 1984) or explain how fieldwork assists students achieve learning goals (Hutz, Gomes, & McCarthy, 2006;Von Dras & Miller, 2002). Reddy and Hill (2002) conducted focus groups with 32 psychology majors and discovered that students acquire communication skills, timemanagement, and responsibility through participation in an internship.…”
Section: Introductionmentioning
confidence: 99%
“…Courses have a minimum teaching load of 4000 hours which are usually taught in 5-year undergraduate programmes that include 2 years of internship. The course content is mainly generalist in nature, with subjects spanning all areas of the discipline: neurophysiology, psychobiology, social psychology, clinical psychology, developmental psychology, health psychology and organizational psychology (Hutz et al, 2006). However, they must offer a minimum of two 'emphases'.…”
Section: Introductionmentioning
confidence: 99%